Glycyrrhizic acid: extraction, screening and evaluation of anti-inflammatory property - Swati Chauhan; Neha Gulati; Upendra Nagaich
Objective: Glycyrrhizic acid is a widely used medicinal component as an anti-inflammatory agent, anti ulcer agent, anti-allergy agent and anti-psoriatic agent. The present investigation deals with the extraction of glycyrrhizic acid from licorice roots and evaluating its in-vitro anti inflammatory activity. Methods: Glycyrrhizic acid was extracted using the procedure of maceration. The extract was evaluated for its physicochemical property, biochemical tests and phytochemical properties. The Ii vitro anti- inflammatory activity was evaluated by albumin denaturation technique Results: The results showed that the ash value and the extractive values for the extract were found to be in the limit as given by Ayurvedic Pharmacopoeia of India. Presence of flavonoids, saponins and triterpinoids were identified in the extract from phytochemical parameters. Thin layer chromatographic technique showed a retention value of 0.5 cm. The percentage inhibition showed that the extract is having some potential of healing inflammation. Conclusion: Glycyrrhizic acid was successfully extracted from licorice roots. The evaluation parameters showed the presence of less impurity in the extract, with the potential of having anti-inflammatory property.